Recalibrating international relations analysis: State fragility, big men and local power amidst external power interests in Somalia and Sudan - Ylönen, A. (African Security Review)
The Horn of Africa has been a target of external power interests for centuries. In the last two decades, the strategic interest of regional middle powers has increased significantly. This has involved attempts to extend influence through strategic partnerships with Horn states and non-state actors. The realist international relations literature focusing on this reality commonly depicts the Horn as a great and middle power ‘playing field’ or a ‘chessboard’. However, this article argues that such a view is fundamentally flawed and misrepresents the power dynamics in the Horn of Africa. Considering the Horn’s main state and societal actors as mere proxies of great or middle power patrons crucially disregards their local power, which buttresses their domestic position and agency in their relationships with external partners and adversaries. This article calls for a recalibration of the realist international relations analysis on the Horn of Africa by recentring it on the internal political dynamics of states. It draws on data collected through years of field and desk research and governance-focused indexes, and emphasises the agency of the Horn’s big men and the implications of their local power in the context of external power interests through an empirical analysis of Somalia and Sudan.